Teknik Era Bisu dalam Visualisasi Film The Artist - Agustinus Dwi Nugroho (PANTUN, 2019)
The focus of the study is on how the process of fi lmmaker in producing his works. Especially on the technology of silent fi lm to become the cinematic techniques in visualizing the present fi lms. Narratively, this study analyzes the small portion of the fi lm through coding system, namely, descriptive code and interpretative code in order to obtain the pa" ern of the codes. Meanwhile, the use of silent fi lm techniques is also analyzed technically.The narrative aspect of The Artist visualizes the actor of silent fi lm in his up and down moments. Narratively, the plot of this fi lm moves regarding with the lives of the main character (George Valentin). The cinematic aspect applies silent fi lm technique. One of them is seen through the black and white coloring. The coloring technique is signifi cant to build the atmosphere and the tone of the fi lm. The technique of this silent fi lm is the milestone for the emergence of the style of silent fi lm which becomes the model mode in producing fi lm.Keywords: silent fi lm technique, The Artist fi lm, narrative, cinematic